Cocoa plantation carbon stock at different years after planting (5, 10, 15) in Tomoni Beringin Jaya Village, East Luwu, South Sulawesi, Indonesia. Issue 1 (November 2021) - Nahdia,; Paembonan, S A; Nasaruddin,
Abstract: This study aimed to determine cocoa carbon stocks based on the conditions of cocoa plantations in Tomoni Beringin Jaya Village, East Luwu, South Sulawesi, Indonesia. Carbon stocks were estimated from aboveground and belowground biomass using an allometric methodology. Sample sites were cocoa plantations; sampling intensity was 30% of the land planted with cocoa for 5 years (n = 214), 10 years (n=229) and 15 years (n=329), soil sampling disturb (measure soil organic carbon), un disturb (measure bulk soil bulk density) and soil bulk density at depth 0-10 cm and 10-20 cm. Carbon stock cocoa aboveground biomass at the age of 5 years (M45) was 1.89 ton C ha -1 and belowground biomass was 0.56 ton C ha -1 with proportion 77.19%:22.81%. Carbon stock cocoa aboveground biomass at the age of 10 year (BR25) was 3.66 ton C ha -1 and belowground biomass 1.01 ton C ha -1 with a proportion 78.37%:21.63%. Carbon stock cocoa aboveground biomass at 15 year (BR25) was 4.58 ton C ha -1 and belowground biomass of 1.21 ton C ha -1 with a proportion 79.07%:20.93%. Cocoa carbon stock at 5 year, 10 year, and 15 year respectively increased, nevertheless mean annual carbon stock cocoa decreased in 5 years cocoa aboveground biomass was 0.37 ton C ha -1 and belowground biomass 0.11 tonCa -1 . Carbon stock cocoa 10 year aboveground biomass 0.36 ton C ha -1 and belowground biomass 0.10 ton C ha -1 . Carbon stock cocoa 15 year aboveground biomass 0.30 ton C ha -1 and belowground biomass 0.08 ton C ha -1 . Soil organic carbon showed dynamic under different year cocoa plantation. Soil organic carbon in cocoa plantation age 5 year was 0.031 tonCha -1, cocoa plantation age 10 year was 0.034 ton C ha - 1, and cocoa plantation age 15 year was 0.043 ton C ha -1 .